THEORETICAL FUNDAMENTALS OF INNOVATIVE ENTERPRISE RESTRUCTURING - LARIONOVA, KATERINA; DONCHENKO, TETYANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article investigates and highlights the approaches to defining the concept of "enterprise restructuring" depending on the state of its development strategy, substantiates the economic essence of the concept of "innovation" and "innovative activity ". Based on the combination of characteristics and essence of these concepts, the definition of "innovative restructuring" is formalized and the author's definition is proposed. It is determined that innovative restructuring is practiced not so much in crisis enterprises as in enterprises that operate stably and seek radical quality change. When making changes, the main ones should be the innovative orientation of management systems, production flexibility, purposeful and effective innovations. It is proved that for effective and complex innovative restructuring it is necessary to improve the enterprise management system by developing and implementing new principles, methods and management structures. That is why the elements of the mechanism of innovative restructuring of the enterprise were singled out and the functions of innovative restructuring were defined and detailed, which allowed to improve the conceptual and categorical apparatus of this economic concept. It is proved that the condition for effective implementation of innovations in the framework of restructuring is the presence of innovative potential in the enterprise. In addition, the transition of the enterprise from one stage of development to another involves the gradual development of innovation potential. This explains the close relationship and mutual influence between innovative restructuring and the innovative potential of the enterprise. Thus, the achievement of goals in the process of enterprise restructuring will depend on the ability to form an effective system of innovation management and the level of innovation potential of the enterprise - its ability to achieve innovative goals.
Keywords: enterprise restructuring; innovation; innovative activity; innovative restructuring; innovative potential; mechanism of innovative restructuring